Surfactant-Assisted Synthesis of NiO-ZnO and NiO-CuO Nanocomposites for Enhanced Photocatalytic Degradation of Methylene Blue Under UV Light Irradiation - Weldekirstos, Hulugirgesh Degefu; Habtewold, Birtukan; Kabtamu, Daniel Manaye (Frontiers in Materials, 2022)
Graphical Abstract